Case report: A rare case of renal epithelioid angiosarcoma - Zhai, Jiancheng; Che, Bangwei; Shen, Jun; Cen, Kangming; Zhang, Yusui; Li, Tenxian; Tang, Dongxin; Tang, Kaifa (Frontiers in Oncology, 2024)
Primary renal epithelioid angiosarcoma (EAS) is extremely rare and carries a poor prognosis. Herein, we present a case of renal EAS in an 81-year-old male patient who complained of hematuria for 1 year. A computerized tomography (CT) scan revealed an occupying lesion at the upper pole of the left kidney, with scattered calcifications, along with retroperitoneal lymph node metastasis and possible lung metastasis. A laparoscopic palliative nephrectomy was performed, and postoperative pathology confirmed a malignant tumor with necrosis in the left kidney. Immunohistochemistry (IHC) revealed positive expression for CD31, CD10, and vimentin, consistent with the diagnosis of EAS. Although EAS is a rare, aggressive, and often misdiagnosed condition, IHC can help confirm its diagnosis, and in our case, the scattered calcifications observed on CT imaging might be helpful in its differential diagnosis.